A PEGylation method of fabricating bioprosthetic heart valves based on glutaraldehyde and 2-amino-4-pentenoic acid co-crosslinking with improved antithrombogenicity and cytocompatibility. (May 2022) - Ding, Kailei; Zheng, Cheng; Huang, Xueyu; Zhang, Shumang; Li, Meiling; Lei, Yang; Wang, Yunbing
Abstract: With the development of diagnostic techniques, the incidence of bioprosthetic heart valve thrombosis (BHVT) is found to be seriously underestimated. Developing bioprosthetic heart valves (BHVs) that have good hemocompatibility without sacrificing other properties such as hydrodynamics and durability will be an effective strategy to alleviate BHVT. In this study, we developed a PEGylation method by co-crosslinking and subsequent radical polymerization. 2-amino-4-pentenoic acid was used to introduce carbon-carbon double bonds for glutaraldehyde crosslinked pericardia. Then poly (ethylene glycol) diacrylate (PEGDA) was immobilized on pericardia by radical polymerization. A comprehensive evaluation of the modified pericardia was performed including structural characterization, hemocompatibility, cytocompatibility, mechanical properties, component stability, hydrodynamic performance and durability of the BHVs. The modified pericardia significantly reduced platelet adhesion by more than 75% compared with traditional glutaraldehyde crosslinked pericardia. Cell viability in the modified pericardia group was nearly 5-fold higher than that in glutaraldehyde crosslinked pericardia. The hydrodynamic performance met the requirements of ISO 5840–3 under physiological aortic valve conditions and its durability was proved after 200 million cycles of accelerated fatigue test. In conclusion, PEGDA modified pericardia exhibited improved antithrombogenicity and cytocompatibility properties compared with glutaraldehyde crosslinked pericardia. Statement of significance: Bioprosthetic valve (BHV) implantation requires BHV to be structurally stable as well as biocompatible in vivo . Traditional glutaraldehyde crosslinking method prepared BHV suffers from severe cytotoxicity, thrombosis, and calcification. BHV modification methods that have simultaneously improved structural stability and biocompatibility were rarely reported. Here, we proposed a PEGylation method for BHV based on co-crosslinking strategy that could improve its structural stability as well as hemocompatibility. We take the advantage of high efficiency of glutaraldehyde crosslinking and demonstrate the feasibility and superiority of the PEGylated strategy, offering a promising option in glutaraldehyde-based BHV fabrication in the future. Graphical abstract: Image, graphical abstract